The product rovibrational and spin-orbit state dependent dynamics of the complex reaction H+CO2 -> OH((2)Pi;nu,N,Omega, f)+CO: Memories of a lifetime - Brouard, M; Hughes, D; Kalogerakis, K; Simons, J (2000)
The product-state-resolved dynamics of the reaction H+CO2→OH(2II;νN,Ω,f)+CO have been explored in the gas phase at 298 K and center-of-mass collision energies of 2.5 and 1.8 eV (respectively, 241 and 174 kJ mol-1), using photon initiation coupled with Doppler-resolved laser-induced fluorescence detection. A broad range of quantum-state-resolved differential cross sections (DCSs) and correlated product kinetic energy distributions have been measured to explore their sensitivity to spin-orbit, A-doublet, rotational and vibrational state selection in the scattered OH. The new measurements reveal a rich dynamical picture. The channels leading to OH(Ω,N ∼ 1) are remarkably sensitive to the choice of spin-orbit state: Those accessing the lower state, Ω=3/2, display near-symmetric forward-backward DCSs consistent with the intermediacy of a short-lived, rotating HOCO (X̃2A') collision complex, but those accessing the excited spin-orbit state, Ω=1/2, are strongly focused backwards at the higher collision energy, indicating an alternative, near-direct microscopic pathway proceeding via an excited potential energy surface. The new results offer a new way of reconciling the conflicting results of earlier ultrafast kinetic studies. At the higher collision energy, the state-resolved DCSs for the channels leading to OH(Ω,N ∼ 5-11) shift from forward-backward symmetric toward sideways-forward scattering, a behavior which resembles that found for the analogous reaction of fast H atoms with N2O. The correlated product kinetic energy distributions also bear a similarity to the H/N2O reaction; on average, 40% of the available energy is concentrated in rotation and/or vibration in the scattered CO, somewhat less than predicted by a phase space theory calculation. At the lower collision energy the discrepancy is much greater, and the fraction of internal excitation in the CO falls closer to 30%. All the results are consistent with a dynamical model involving short-lived collision complexes with mean lifetimes comparable with or somewhat shorter than their mean rotational periods. The analysis suggests a potential new stereodynamical strategy, "freeze-frame imaging," through which the "chemical shape" of the target CO2 molecule might be viewed via the measurement of product DCSs in the low temperature environment of a supersonic molecular beam. © 2000 American Institute of Physics.